Intorno a Boccaccio/Boccaccio e dintorni 2021 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 9-10 settembre 2021) - BERTE', MONICA (Studi e saggi, 2022)
Intorno a Boccaccio/Boccaccio e dintorni 2021 collects the Proceedings of the Seminar that took place in Certaldo Alta on 9-10 September 2021. The Seminar, now in its eighth edition, is configured not only as one of the main activities of the Ente Nazionale Giovanni Boccaccio, but as an international event, whose importance is confirmed by the continuous increase in citations in the scientific bibliography. The 2021 edition also qualifies for the relief and variety of the topics covered, for the merging and intertwining of historical-literary, philological, linguistic skills, which lead to reflect on important topics of Boccaccio's culture and sources and on his works.